APPROACHES FOR A MODEL OF POPULATION UROLOGICAL SCREENING BASED ON TELEMEDICINE TECHNOLOGIES - O. I. Apolikhin; A. V. Sivkov; I. A. Shaderkin; A. V. Vladzymyrskyy; V. A. Shaderkina; D. A. Voytko; M. Yu. Prosyannikov (Вестник урологии, 2017)
Background. The prostate cancer wins a first place among men oncological diseases by rates of an incidence and mortality. The late detection is a main reason of high mortality (approximately 52,0% patients starts treatment after more than 1 year of symptoms existence). A screening allows improve detection dramatically, but current methods of screening almost impossible to use widely. System of oncological urology needs new effective approaches for population screening. Aim. To develop empirical approaches for a model of population urological screening with a telemedicine as a key element. Material and methods. The research are backgrounded on systemic approach. Methods of analysis, synthesis and information modeling were used. Methodological documents recognized by WHO used for model evaluation. Results and discussion. National program of an urological screening should be backgrounded on methods of selective staged examinations of target population group, telemedicine technologies must be a key integrative element. The formal information model of prostate cancer telemedicine screening was developed. The key element of the model is an information system which consist from: - web-questionnaires and online risk assessment forms, - Electronic health records module, - Laboratory module, - PACS. The model was developed according to criterion for screening programs recognized by WHO. Conclusion. Approaches for an urological screening organization had been developed empirically. All issues joints the formal information model of prostate cancer telemedicine screening. The model are valid according to WHO methodological documents. Further researches will be focused on model introduction and evaluation in the field.